2014
DOI: 10.1007/s10120-014-0368-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and management of positive horizontal margin in early gastric cancer resected by en bloc endoscopic submucosal dissection

Abstract: Background Although endoscopic submucosal dissection (ESD) is a widely accepted treatment for early gastric cancer (EGC), there is no consensus regarding the management of positive horizontal margin (HM) despite en bloc ESD. The aim of the current study was to identify the risk factors and optimal management of positive HM in EGCs resected by en bloc ESD. Methods A total of 890 consecutive patients with 1,053 intramucosal EGCs resected by en bloc ESD between April 2005 and June 2011. Clinicopathological data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
0
31
1
Order By: Relevance
“…Numata et al [8] argued that the reason why some patients with a positive lateral margin never experienced recurrence was that these so-called positive margins were actually caused by crushing-or burn-related damages. As such, the positive margin often occurred in the upper-third portion of the stomach, where it is difficult to perform ESD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numata et al [8] argued that the reason why some patients with a positive lateral margin never experienced recurrence was that these so-called positive margins were actually caused by crushing-or burn-related damages. As such, the positive margin often occurred in the upper-third portion of the stomach, where it is difficult to perform ESD.…”
Section: Discussionmentioning
confidence: 99%
“…There were 7,562 participants involved in total. Moreover, there were 34 patients and 22 patients who did not meet either the absolute or the expanded criteria in the studies conducted by Kosaka et al [6] and Numata et al [8] , respectively. Similarly, Oda et al [9] only observed 2,806 patients' long- term outcomes, so the present meta-analysis included a total of 6,687 patients.…”
Section: Study Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retrospective studies have tried to identify risk factors to positive HMs [19-21]. Kakushima et al [20] reported three main reasons for positive HMs after resection: lesions with a flat spreading area not included in the marking, lesions with an unexpected nearby lesion, and lesions with lateral extension in the submucosa under a non-cancerous mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…After that, Sekiguchi et al [19] identified a cancer-positive lateral margin length ≥6 mm as an independent risk factor for local recurrence after ESD (with a sensitivity and specificity for a 5-year risk of developing local recurrence of 66.7  and 95.6 %, respectively). Recently, Numata et al [21] recognised that location of the tumour in the upper third of the stomach and lesions not matching the absolute indication criteria were independent risk factors for positive HMs. In this study, expertise with digital chromoendoscopy improved along with the ESD learning curve, and the regular use of high-definition endoscopy in the last period can partially explain highly positive HMs in the beginning.…”
Section: Discussionmentioning
confidence: 99%